Evaluating the coverage and quality of nutrition programs via a bottom‐up approach: A secondary analysis of real‐time data from an end‐user monitoring system in Ethiopia - Anne‐Sophie Donzé; Abiy Tefera; Kaleab Baye; Stéphane Arnaud; Stanley Chitekwe; Arnaud Laillou (Wiley, 2024)
Abstract Over the last two decades, great efforts and investments have been made in Ethiopia to ensure that all children have equal access to nutrition services in health facilities. While quality health systems are a prerequisite for quality nutrition services, little attention has been given to the evaluation of the supply and delivery services. The purpose of the study was to evaluate the coverage and quality of the nutrition‐specific interventions delivered through the health system. Using an end‐user monitoring (EUM) system, we monitored the delivery of nutrition‐specific interventions in 500 districts, having 2514 health facilities distributed throughout Ethiopia. Data were collected through third‐party monitors between August 2020 and 2021. Roughly 90% of health facilities were performing severe acute malnutrition management in line with the national guideline/protocol, and 2/3 of the assessed facilities were delivering iron and folic acid, vitamin A supplementation and deworming. A third of the messages on AMIYCN were retained by beneficiaries. Warehouse conditions were good in 64.3% of the facilities, but only 22% had good recording practices and about half had problems related to the quality and availability of nutrition supplies. Most beneficiaries were satisfied with the nutrition supplies and service delivered at the health facility level. This study also suggests the relevance of an EUM system to assess the quality of nutrition service delivery and its related supply management, as well as to improve the implementation of nutrition interventions as a decision‐making tool.